The taxation in South Africa of business profits of controlled foreign companies: in conflict with international law? - Marais, Retha (Centre for Law and Society, 2026)
The face of commerce has become progressively more globalised in the past decades, facilitated by among other factors, telecommunication improvements and the ease and speed of travel.1 An increasing number of South African companies are expanding their business internationally, and directly controlled foreign investment is increasing consistently.2 Whilst the economic activity generated by the global expansion of South African companies is positive, it creates a problem for the South African government, in that the flight of capital may erode the domestic tax base. To address this problem, South Africa replaced source-based taxation with residence-based taxation as of 1 January 2001, leading to the taxation of its residents' worldwide income.